Case report: binaural beats music assessment experiment - Krasnoff, Elizabeth; Chevalier, Gaétan (Frontiers in Human Neuroscience, 2023)
We compared the effects of relaxation music to the effects of relaxation music plus inaudible binaural beats, measuring EEG, HRV, and GSR. All four subjects experienced an improvement in brain function and a calmer brain after adding binaural beats to brown noise or to music plus brown noise. Most also showed an improvement in microcirculation or cardiovascular score after listening to music plus brown noise and binaural beats. Binaural beats seem to have profound effects on the physiology of subjects and since the beats were not audible, these effects could not be attributed to the placebo effect. These results are encouraging in terms of developing musical products incorporating binaural beats to affect human neural rhythms and corollary states of consciousness and warrant further research with more subjects and different frequencies of binaural beats and different music tracks.